Pengaruh Pemberian Jus Mentimun Air Kelapa Muda Terhadap Penurunan Tekanan Darah Lansia Hipertensi Di Panti Sosial Tresna Werdha “PUSPAKARMA” Mataram - Nimade Dwi Anjani; Niketut Sri Sulendri; Yuli Laraeni; Iketut Swirya Jaya (Jurnal Gizi Prima (Prime Nutrition Journal), 2017)
Background. Hypertension or high blood pressure is an increase in systolic blood pressure equal to or greater than 140 mmHg and diastolic blood pressure is equal to or greater than 90 mmHg. Hypertension often occurs in elderly considering almost most of the function of the organs began to decline with age. Cucumber and coconut water contain high enough potassium which can help lower blood pressure. Combination of juice of young coconut cucumber water can increase potassium input in the body so it can lower blood pressure, especially in elderly group.  Research Purposes. This study aims to determine the effect of young coconut water cucumber juice on the decrease in hypertensive blood pressure at the Social Institution Tresna Werdha "Puspakarma" Mataram. Research Methods. Quasy-experimental research type with Non Equivalent Control Group design. Sample in this research is hypertensive elder counted 30 people with technique of total sampling type. The data collected are data of identity of sample which include age, sex, weight and height data to know the nutritional status of sample, history of hypertension disease in family, smoking habit, coffee consumption, alcohol consumption, antihypertensive drug consumption, physical activity, intake data Nutrients (fat, carbohydrate, potassium, sodium and fiber), as well as data on blood pressure test both systolic blood pressure and diastolic blood pressure before and after treatment with average juice of young coconut cucumber of ± 200 ml with frequency one time Day for five days treatment. Research Result. The results showed a decrease in systolic blood pressure of 9.33 mmHg (p = 0,000) and diastolic blood pressure of 3 mmHg (p = 0.055). Conclusion. The conclusion is that there is an effect on systolic blood pressure but no effect on diastolic blood pressure before and after given coconut water cucumber juice.